COMPARISON OF KARHUNEN-LO`EVE EXPANSION AND MONTE CARLO SIMULATION METHODS IN MODELING THE DYNAMICS OF A HALF-CAR SUSPENSION SYSTEM - Dilyorjon Yuldashev Turin Polytechnic University in Tashkent, Uzbekistan (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
This paper presents a comparative study of two prominent uncertainty quan-tification methods: the Karhunen-Lo`eve Expansion (KLE) and Monte Carlo Simu-lation (MCS). The application of these methods is demonstrated using the half-car suspension system, a widely studied model in vehicle dynamics. The KLE method’s computational efficiency and its ability to provide analytical insights are compared with the brute-force accuracy of the Monte Carlo approach. Results indicate that KLE significantly reduces computation time while maintaining sufficient accuracy, making it a preferred choice in many engineering applications.